233k views
5 votes
Please help ASAP!!! Thank you!!!

Please help ASAP!!! Thank you!!!-example-1
User Leech
by
5.5k points

2 Answers

6 votes

(1)

=(3x+2)(x-1)

=3x(x-1)+2(x-1)

=3x^-3x+2x-2

=3x^-x-2

(2)

=(x-5) (2x+3)

=x(2x+3)-5(2x+3)

=2x^+3x-10x-15

=2x^-7x-15

(3)

=(2x+5) (3x-2)

=2x(3x-2)+5(3x-2)

=6x^-4x+15x-10

=6x^+11x-10

User Emirhan
by
4.5k points
5 votes

Explanation:

1) = Solution

(3x+2)(x-1) = 3x^2 - 3x+2x-2

= 3x^2 - x - 2

2) = (x-5)(2x+3)

= 2x^2 + 3x - 10x - 15

= 2x^2 - 7x - 15

3) = (2x+5)(3x-2)

= 6x^2 - 4x + 15x - 10

= 6x^2 + 11x - 10

User Laura Calinoiu
by
5.1k points